Intramural mapping of intramural septal ventricular arrhythmias. (5th March 2022) - Tam, Tsz‐kin; Ghannam, Michael; Liang, Jackson J.; Attili, Anil; Cochet, Hubert; Jais, Pierre; Juhoor, Mehdi; Latchamsetty, Rakesh; Jongnarangsin, Krit; Morady, Fred; Bogun, Frank
Abstract: Background: Intramural ventricular arrhythmias (VAs) can originate in patients with or without structural heart disease. Electrogram (EGM) recordings from intramural sources of VA have not been described thoroughly. Objective: We hypothesized that the presence of scar may be linked to the site of origin (SOO) of focal, intramural VAs. Methods: In a series of 21 patients (age: 55 ± 11 years, 12 women, mean ejection fraction 43 ± 14%) in whom the SOO of intramural VAs was identified, we analyzed bipolar EGM characteristics at the SOO and compared the findings with the endocardial breakout site. The patients were from a pool of 86 patients with intramural VAs referred for ablation. Results: In 16/21 patients intramural scarring was detected by cardiac magnetic resonance (CMR) imaging In patients in whom the intramural SOO was reached, intramural bipolar EGMs showed a lower voltage and had broader EGMs compared to the endocardial breakout sites (0.97 ± 0.56 vs. 2.28 ± 0.15 mV, p = .001; and 122.3 ± 31.6 vs. 96.5 ± 26.3 ms, p < .01). All intramural sampled sites at the SOO had either low voltage or broad abnormal EGMs. The activation time was significantly earlier at the intramural SOO than at breakout sites (−36.2 ± 11.8 vs. −23.2 ± 9.1 ms, p < .0001). Conclusions: Sites of origin of intramural VAs with scar by CMR display EGM characteristics of scarring, supporting that scar tissue localizes to the SOO of intramural outflow tract arrhythmias in some patients. Scarring identified by CMR may be helpful in planning ablation procedures in patients with suspected intramural VAs.